Regulatory Ethics in The Context of Mobile Communications and AI in Society - Claudia Oktaviani Yuwono; Erik Reyhan; La Rawi La Hara (Jurnal Indonesia Sosial Sains, 2025)
The rapid advancement of mobile technology and artificial intelligence (AI) has brought about significant changes in the way social communication is carried out throughout Indonesia. Although this technology has a significant positive impact, challenges related to ethical regulations, especially in terms of protecting personal data safety, taste and clarity, are a matter of concern. This research seeks to understand the ethical regulations and their implementation that must be carried out so that this communication technology does not harm society. This research reviews the application of regulatory ethics in the field of mobile applications and AI using the theories of ambiguity, negative morality, fairness, and vulnerability. Methods include a literature review of updated peer-reviewed articles as well as data points and statistics from secondary articles on how past applications of Mobile-AI changed Indonesia's social communication patterns. The findings show that current regulations are not effective at protecting user privacy; therefore, the study concludes by recommending stricter policy planning on the use of AI technology to engage and instill public trust.